2020
DOI: 10.2147/dddt.s229607
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inhibitory Effect of Curcumin on Artery Restenosis Following Carotid Endarterectomy and Its Associated Mechanism in vitro and in vivo</p>

Abstract: Objective: The present study aimed to assess the effect of curcumin (Cur) on carotid artery restenosis following carotid endarterectomy (CEA) and its associated mechanism in vivo and in vitro. Methods: Ang II was used to induce excessive proliferation of rabbit aortic smooth muscle cells (CCC-SMC-1) in order to establish a hemadostenosis cell model. Similarly, the animal model of carotid artery restenosis was established by carotid artery gas drying injury combined with high-fat feed prior to CEA. CCC-SMC-1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…[29][30][31] In addition, some signaling pathways spread through b-RAF/MEK/ERK in various cellular processes, such as cell growth, differentiation and apoptosis. [32][33][34] Our research was consistent with these data, suggesting that double knockdown of MAGOH and MAGOHB inhibited the growth of gastric cancer cells via downregulation of b-RAF/MEK/ERK signaling. Frankly speaking, there is a limitation in this research: This study focused only on RAF/MEK/ERK signaling pathway so far.…”
Section: Discussionsupporting
confidence: 88%
“…[29][30][31] In addition, some signaling pathways spread through b-RAF/MEK/ERK in various cellular processes, such as cell growth, differentiation and apoptosis. [32][33][34] Our research was consistent with these data, suggesting that double knockdown of MAGOH and MAGOHB inhibited the growth of gastric cancer cells via downregulation of b-RAF/MEK/ERK signaling. Frankly speaking, there is a limitation in this research: This study focused only on RAF/MEK/ERK signaling pathway so far.…”
Section: Discussionsupporting
confidence: 88%
“…hypolipidemic, and anti-atherosclerotic effects, with minimal toxic side effects. [7][8][9][10] It has also been reported that CUR inhibits apoptosis of VSMCs 11 and is involved in regulating VC 12,13 by inhibiting JNK/Bax signaling pathway-mediated apoptosis. 14 While there is increasing evidence that CUR can protect the cardiovascular system, 15,16 the molecular mechanism by which CUR attenuates VC remains unknown.…”
Section: Impact Statementmentioning
confidence: 97%